Oxidative stress mediates the inhibitory effects of Manzamine A on uterine leiomyoma cell proliferation and extracellular matrix deposition via SOAT inhibition - Li-Chun Lin; Hsin-Yi Chang; Tzu-Ting Kuo; Hsin-Yuan Chen; Wen-Shan Liu; Yii-Jwu Lo; Shih-Min Hsia; Tsui-Chin Huang (Redox Biology, 2023)
Uterine fibroids, the most common benign tumors of the myometrium in women, are characterized by abnormal extracellular matrix deposition and uterine smooth muscle cell neoplasia, with high recurrence rates. Here, we investigated the potential of the marine natural product manzamine A (Manz A), which has potent anti-cancer effects, as a treatment for uterine fibroids. Manz A inhibited leiomyoma cell proliferation in vitro and in vivo by arresting cell cycle progression and inducing caspase-mediated apoptosis. We performed target prediction analysis and identified sterol o-acyltransferases (SOATs) as potential targets of Manz A. Cholesterol esterification and lipid droplet formation were reduced by Manz A, in line with reduced SOAT expression. As a downstream target of SOAT, Manz A also prevented extracellular matrix deposition by inhibiting the β-catenin/fibronectin/metalloproteinases axis and enhanced autophagy turnover. Excessive free fatty acid accumulation by SOAT inhibition led to reactive oxygen species to impair mitochondrial oxidative phosphorylation and trigger endoplasmic reticulum stress via PERK/eIF2α/CHOP signaling. The inhibitory effect of ManzA on cell proliferation was partially restored by PERK knockdown and eliminated by tauroursodeoxycholic acid, suggesting oxidative stress plays a critical role in the mechanism of action of Manz A. These findings suggest that targeting SOATs by Manz A may be a promising therapeutic approach for uterine fibroids.